2005
DOI: 10.1111/j.1600-0447.2005.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

HPA axis normalization, estimated by DEX/CRH test, but less alteration on cerebral glucose metabolism in depressed patients receiving ECT after medication treatment failures

Abstract: Depressed patients who failed trials of antidepressant medication showed a remission with ECT that was accompanied by resolution of HPA dysregulation. However, measures of cerebral brain metabolism did not resolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…brain regions (Prohovnik et al, 1986;Rosenberg et al, 1988;Scott et al, 1994;Silfverskiöld et al, 1986). Studies that measured the long-term effects of ECT also found a decrease in CBF or glucose metabolism in the frontal, parietal, and temporal lobes (Henry et al, 2001;Nobler et al, 2001;Yuuki et al, 2005;Suwa et al, 2012). Three studies reported an increase in regional blood flow in similar cortical regions (Bonne et al, 1996;Mervaala et al, 2001;Suwa et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…brain regions (Prohovnik et al, 1986;Rosenberg et al, 1988;Scott et al, 1994;Silfverskiöld et al, 1986). Studies that measured the long-term effects of ECT also found a decrease in CBF or glucose metabolism in the frontal, parietal, and temporal lobes (Henry et al, 2001;Nobler et al, 2001;Yuuki et al, 2005;Suwa et al, 2012). Three studies reported an increase in regional blood flow in similar cortical regions (Bonne et al, 1996;Mervaala et al, 2001;Suwa et al, 2012).…”
Section: Discussionmentioning
confidence: 92%
“…In this way, SPECT and PET studies on the effects of ECT on brain activities in depressed patients have led to conflicting results, ranging from overall decrease [18][19][20] to increase [21]. In addition, Yuuki et al [22] demonstrated hypometabolism in some parts of prefrontal regions and hypermetabolism in the parietal and occipital lobes after ECT treatment. In addition, several genes involved in the metabolic regulation are up-regulated chronically after ECS, mainly in the hippocampus [12].…”
Section: Tbars Acutementioning
confidence: 96%
“…Successful ECT treatment is associated with normalization of hypothalamic-pituitary-adrenal (HPA) axis abnormalities in this patient population [3, 4]. The hippocampus is a limbic brain region that is particularly sensitive to excitotoxic insults that arise from elevated levels of circulating glucocorticoids, and it plays a key role in the stress response by providing negative feedback inhibition over the HPA axis[5-7].…”
Section: Introductionmentioning
confidence: 99%